ANALISIS FIKSI KADO UNTUK PUTRI UNGU DAN SURI CUCU KAKEK DULHAK: TINJAUAN STRUKTURALISME - Yulia Pebriani, M.Pd (Jurnal Gramatika, 2015)
Growing exprience and personal success showed the children a variety of other ways to control their emotions, overcome fear, develop trust, overcoming the desire to maintain the way they are right, develop acceptable interations with peers and adults  are sure to occur and not inevitable. In this case carried out by researchers, for example in the areas of socia, psychologi, and literature. In the study of literature, structuralisme is important in the study, because this principle wear every element associated with other elements. In children’s literature, the outhers raise the study of how views on the structure of the literary work litertaure contains exploration of the truth of humanity. Litertaure also offers a shred story that stimulates the readers to do something. Reader especially children developing new fantasy arrives and receive children developing new fantasy arrives and receive all kinds of stories off, whether the story makes sense or not. As a literary work certainly want to convey a meaning that contain human values. As children  who are able to give readers an understanding based on the growth and development of children.